Distinct Glucocorticoid Receptor Transcriptional Regulatory Surfaces Mediate the Cytotoxic and Cytostatic Effects of Glucocorticoids - Rogatsky, Inez (American Society for Microbiology, 1999)
Glucocorticoids act through the glucocorticoid receptor (GR), which can function as a transcriptional activator or repressor, to elicit cytostatic and cytotoxic effects in a variety of cells. The molecular mechanisms regulating these events and the target genes affected by the activated receptor remain largely undefined. Using cultured human osteosarcoma cells as a model for the GR antiproliferative effect, we demonstrate that in U20S cells, GR activation leads to irreversible growth inhibition, apoptosis, and repression of Bcl2. This cytotoxic effect is mediated by GR’s transcriptional repression function, since transactivation-deficient mutants and ligands still bring about apoptosis and Bcl2 down-regulation. In contrast, the antiproliferative effect of GR in SAOS2 cells is reversible, does not result in apoptosis or repression of Bcl2, and is a function of the receptor’s ability to stimulate transcription. Thus, the cytotoxic versus cytostatic outcome of glucocorticoid treatment is cell context dependent. Interestingly, the cytostatic effect of glucocorticoids in SAOS2 cells involves multiple GR activation surfaces. GR mutants and ligands that disrupt individual transcriptional activation functions (activation function 1 [AF-1] and AF-2) or receptor dimerization fail to fully inhibit cellular proliferation and, remarkably, discriminate between the targets of GR’s cytostatic action, the cyclin-dependent kinase inhibitors p21(Cip1) and p27(Kip1). Induction of p21(Cip1) is agonist dependent and requires AF-2 but not AF-1 or GR dimerization. In contrast, induction of p27(Kip1) is agonist independent, does not require AF-2 or AF-1, but depends on GR dimerization. Our findings indicate that multiple GR transcriptional regulatory mechanisms that employ distinct receptor surfaces are used to evoke either the cytostatic or cytotoxic response to glucocorticoids.